Physical, Chemical, and Microbiological Properties of Soil under Different Plant Covers in the Seridó Desertification Region in the Brazilian Semiarid - Martins,Adriana Ferreira (2019)
ABSTRACT The Seridó Desertification Region is a result of inadequate management of the native Caatinga vegetation, which generated degraded areas with little or no capacity for plant production. The area has experienced a succession of different land uses, but little is known about the impact of these changes. The present study tested the hypothesis that the intense degradation of the Caatinga drastically decreased vegetal biomass production, which favored direct soil exposure and resulted in a lower abundance and diversity of species and groups of vegetation as well as microorganisms. This study aimed to quantify some of the main physical, chemical, and microbiological properties of Alfisol ( Luvissolo Crômico órtico lítico ) and Entisol ( Neossolo Litólico eutrófico típico ) under different plant covers in the Seridó Desertification Region, in the municipality of Parelhas, in the state of Rio Grande do Norte (RN), Brazil. Three different areas were studied: an area of preserved Caatinga, a recovery area with jurema [ Mimosa tenuiflora (Willd.) Poir.], and a degraded area. Soil samples were collected from the 0.00-0.10 m soil layer and later characterized in terms of their physical and chemical properties. The microbiological characteristics analyzed were microbial activity (microbial biomass carbon and microbial respiration) and glomalin. The soil under the Caatinga vegetation exhibited better properties than the other analyzed soils. Aggregate stability was the physical property with the highest potential for differentiating between areas. Glomalin, which is associated with the presence of mycorrhizae, and which, in turn, is related to the uptake of P, which is often deficient in these soils, was the most discriminating microbiological variable according to an analysis of canonical variables. The total of Ca2+ and Mg2+ was the most discriminating chemical properties, and played a positive role in soil aggregation, especially Ca2+.